Detection of Contaminants of High Environmental Impact by Means of Fluorogenic Probes. Issue 2 (29th February 2016) - García‐Calvo, José; Calvo‐Gredilla, Patricia; Ibáñez‐Llorente, Marcos; Rodríguez, Teresa; Torroba, Tomás
Abstract: This personal account describes our contribution to the design of selective fluorogenic probes for contaminants of high environmental impact. For this purpose, we have developed a new family of highly versatile fluorogenic reagents that were able to show large differences in their fluorescence in the presence of selected analytes. They were used in the preparation of fluorogenic probes for the detection of contaminants of high environmental impact which currently have no good solutions: phosphorylating agents, such as chemical weapons; methyl mercury(II); the cyanide anion; amino‐acid metabolites, such as doping substances; and biogenic amine mimics, such as drugs of abuse and recreational drugs. The development of new materials for specific sensing was achieved by anchoring selected probes to silica nanomaterials, suitable for the selective detection of organic analytes in water for immediate application to toxicological or environmental purposes. Abstract : Detection of contaminants of high environmental impact by means of fluorogenic probes : Selective fluorogenic probes for contaminants of high environmental impact, which were able to show large differences in their fluorescence in the presence of selected analytes, were used in the preparation of fluorogenic probes for the detection of contaminants of high environmental impact which currently have no good solutions: phosphorylating agents, such as chemical weapons; methyl mercury(II); the cyanide anion; amino‐acid metabolites, such as doping substances; and biogenic amine mimics, such as drugs of abuse and recreational drugs.